Study of the motivation and the competitiveness in artisan workshops - Luis Ángel Correa García; Juan Carlos Pino Acevedo; Elsa Ortega de Ávila (Ciencias Administrativas)
This paper studies the artisan workshops that are disappearing and contributes to the understanding of the socio-cultural devaluation suffered by craftsmanship. The objective of this article is to analyze the motivation of the artisan and the competitiveness of the workshops from the theoretical-administrative, behavioral and motivational perspective. The methodology used is quantitative by means of a multiple regression analysis, which studies the independent variables of economic, cultural, family motivation and the business as a way of life with competitiveness as the dependent variable. The main findings show that the artisanal workshops operate at a loss and that economic motivation is the statistically significant variable in business competitiveness. It is concluded that the artisan workshops are being lost, therefore it is necessary to strengthen the purchase of raw materials and investment in machinery.